Database applications semantics proceedings of the IFIP WG 2.6 Working Conference on Database Applications Semantics (DS-6), Stone Mountain, Atlanta, Georgia, U.S.A., May 30-June 2, 1995 - Meersman, Robert; Leo, Mark (Chapman & Hall, 1997)
End-users and non-computer experts are becoming heavily involved in the set-up, management and use of database systems. This book provides the important database design methodologies and implementation technology which should be available for them as well as for computer experts.